Pharmacognostic Evaluation of Hyptis Suaveolens (L.Poit) Lamiaceae - D.A. Dhale2*, G.L. Pachkore1 and (Journal of Ecobiotechnology, 2011)
The present communication deals with the pharmacognostic investigations on the Hyptis Suaveolens (L. Poit) Lamiaceae. The plant is stimulant, carminative, antispasmodic antirheumatic, antisuporitic bath. It is also used for parasitical cutaneous diseases, infection of uterus, and as sudoritic in catarrhal condition, headache, stomach, snuff to stop bleeding of the nose. Macroscopic and microscopic examinations of the organs and differential chemical tests were carried out. The morphology of the entire plant, anatomy of the leaves, stem and root and the physico-chemical standards of the powder in the present study can be used to identify the crude drug. Preliminary phytochemical screening shows the presence of volatile oil, Alkaloid, phenolics, tannin, saponin, protein, carbohydrates etc. Extractive values as well as quantitative estimation of various phytochemicals have been studied for different plant organs.